Analisis Distribusi Dana Bantuan Perum Perumnas dalam Mendukung Tujuan Pembangunan Berkelanjutan (TPB) - Ramdani, Yusep; Sarifah, Fitriana; Azhari, Akmal Haykal; Anbiya, Dhya Nazwa Chaerun; Cholik, Firman Abdul; Rusiani, Hani; Kamila, Irma Nurul; Indriyani, Riska (Universitas Batanghari, 2024)
Organizations and companies as integral elements in society are faced with the responsibility to understand and manage the impact of their operations on the environment, social and economy. The company program, especially BUMN, including Perum Perumnas, which supports the TPB, is the Social and Environmental Responsibility Program (TJSL). This research aims to analyze the role of Perum Perumnas in supporting the Sustainable Development Goals (TPB). This research method is data analysis research or company reports, especially the Perum Perumnas sustainability report for 2021-2022. The results of this research are that Perum Perumnas in 2021-2022 contributed to 10 of the 17 TPB. The order of cumulative TPB aid funds for 2021-2022, from largest to smallest, is TPB 16 (Peace, Justice and Resilient Institutions), TPB 8 (Decent Work and Economic Growth), TPB 6 (Clean Water and Decent Sanitation), SDG 11 (Sustainable Cities and Human Settlements), SDG 4 (Quality Education), SDG 2 (No Hunger), SDG 7 (Clean and Affordable Energy), SDG 14 (Protecting Marine Ecosystems), SDG 5 (Gender Equality), and TPB 10 (Reducing Inequality). The trend in the distribution pattern of Perum Perumnas TPB assistance areas in 2021-2022 follows the project locations handled by Perum Perumnas with the distribution of Perum Perumnas TPB assistance areas still focused on Java Island.